Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/brainsci12060810
|View full text |Cite
|
Sign up to set email alerts
|

Surpass Evolve Flow Diverter for the Treatment of Intracranial Aneurysm: A Systematic Review

Abstract: Purpose: This systematic review aims to summarize the evidence investigating the effectiveness and safety of the Surpass Evolve-Flow Diverter (SE-FD) to treat brain aneurysms. Method: We searched MEDLINE, EMBASE, CINAHL, Web of Science, and Cochrane Library from January 2019 to 29 March 2022. Terms related to the “intracranial aneurysm” and “surpass evolve flow diverter” concepts were used to search the databases; Medical Subject Headings (MeSH) and reference hand search were also utilized. Results: The search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Many papers have demonstrated the effectiveness of the FDs. [3][4][5][6][7][8][9] In a systematic review of the FDs, Briganti et al reported that the rate of aneurysm occlusion progressively increased up to 81.5% over a mean follow-up period of 9-months. They also reported the neurologic morbidity within allowance (3.5%), rate of hemorrhagic complication (2.9%), and rate of non-negligible thromboembolic complications (4.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have demonstrated the effectiveness of the FDs. [3][4][5][6][7][8][9] In a systematic review of the FDs, Briganti et al reported that the rate of aneurysm occlusion progressively increased up to 81.5% over a mean follow-up period of 9-months. They also reported the neurologic morbidity within allowance (3.5%), rate of hemorrhagic complication (2.9%), and rate of non-negligible thromboembolic complications (4.1%).…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent inventions include bioactive and hydrogel-coated GDCs and flow diverters. 7,8 For flow diverters, numerous devices have emerged in two categories: (i) extra-saccular: including the p64, 9 the Pipeline, 10 the Flow Redirection Endoluminal Device (FRED), 11 the Surpass, 12 among others; and (ii) intra-saccular flow diverters: such as the Woven EndoBridge (WEB) 13 and the Contour. 14 The advance of this technology has evolved the application of endovascular therapy for complex aneurysm geometries and even aneurysm locations within the neuro-vasculature.…”
Section: Introductionmentioning
confidence: 99%